2000
DOI: 10.1038/sj.ejhg.5200417
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Marie-Unna hypotrichosis locus to chromosome 8p21 and exclusion of 10 genes including the hairless gene by mutation analysis

Abstract: Marie-Unna hypotrichosis (MU) is a rare autosomal dominant congenital alopecia characterised by progressive hair loss starting in early childhood, often aggravated at puberty and leading to scarring alopecia of variable severity. We have studied three multigeneration families of Belgian, British and French descent. The human genome was screened with microsatellite markers spaced at 10-cM intervals and significant evidence for linkage to the disease was observed on chromosome 8p21, with a maximum two-point lod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Other rare associations reported with MUS include juvenile macular degeneration 137,138 and widely spaced upper incisor teeth. 139 Interestingly, multiple studies [140][141][142][143] have mapped MUS to 8p21, near the Hairless gene mutated in alopecia universalis congenita/APL. However, sequencing has not identified mutations in the Hairless or other candidate genes and alopecia universalis congenita/APL has autosomal recessive rather than dominant inheritance.…”
Section: Genodermatoses With Milia-like Lesionsmentioning
confidence: 99%
“…Other rare associations reported with MUS include juvenile macular degeneration 137,138 and widely spaced upper incisor teeth. 139 Interestingly, multiple studies [140][141][142][143] have mapped MUS to 8p21, near the Hairless gene mutated in alopecia universalis congenita/APL. However, sequencing has not identified mutations in the Hairless or other candidate genes and alopecia universalis congenita/APL has autosomal recessive rather than dominant inheritance.…”
Section: Genodermatoses With Milia-like Lesionsmentioning
confidence: 99%
“…Lefevre et al was also able to demonstrate that the MUHH locus is defined by a broader region defined by markers D8S280 and D8S1839. However, on screening of this locus it was found that MUHH is not due to a mutation within the HR gene nor is MUHH a result of a mutation in nine other genes screened within this locus, including calcineurin A catalytic subunit, SH3 adaptor molecule 1, and human protein phosphatase 2A [9]. Furthermore, it appears as though the locus for MUHH is quite heterogeneous as there has been evidence identifying a locus in region 1p21.1-1q21.3.…”
mentioning
confidence: 97%
“…Identification of the gene responsible for MUHH has proven to be arduous task. Pedigree screening of families suffering from MUHH have defined several loci within chromosome 8 [6][7][8][9] as well as a distinct region in chromosome 1 [10]. Within chromosome 8, van Steensel et al and Hu et al mapped the MUHH locus to a region flanked by markers D8S282 and D8S289 [7,8].…”
mentioning
confidence: 99%
“…[19][20][21] Subsequent studies have confirmed linkage of MUHH to this region. 6,10,11 However, sequencing of the HR gene failed to reveal any disease-associated mutations, and the genetic alteration responsible for MUHH remained unidentified for a decade 6,10,11 after the study of van Steensel et al 12 Causal mutations in U2HR (an inhibitory upstream open reading frame in the 5'-untranslated region of the HR gene) were recently identified in several unrelated MUHH families from various ethnic backgrounds. 17 Functional studies suggest that mutations in U2HR cause gain-of-function of the HR gene and that fine-tuning of the HR protein level is of crucial importance in the control of hair growth.…”
mentioning
confidence: 98%
“…1 Further German MUHH families [5][6][7][8][9] and a number of families of other ethnicities have been reported in recent years. [10][11][12][13][14][15][16][17][18] To identify the causal gene for MUHH, van Steensel et al 12 performed a genomewide linkage study in one Dutch and one British family and mapped the gene for MUHH to chromosome 8p21. This region is close to the human hairless (HR) gene, mutations of which, affecting the coding region or splice sites, are responsible for autosomal recessive congenital atrichia.…”
mentioning
confidence: 99%